Specializations in nursing: the students' perspective - Martin Sever; Branko Bregar (Nurses and Midwives Association of Slovenia, 2015)
Introduction: In Slovenia, nursing students and professionals do not yet have the possibility for specialized career development. The aim of the study is to determine the students' plans for their career development and their views on nursing specialization. Methods: Data were collected via an online questionnaire (alpha = 0.82). The sample included students from three faculties in Slovenia that offer nursing programmes. 385 questionnaires were returned. Data analysis was performed with the SPSS software (version 20.0): t-test, ANOVA, Pearson's correlation and factor analysis. Results: 258 (67 %) of respondents would continue their studies. The specializations most often identified are: urgent medical assistance (20 %), anaesthesiology and intensive therapy (14 %) and surgical care (11 %) and so forth. Older students choose reasons that are linked more to nursing, while younger students choose reasons that are linked more to medicine. It is more characteristic of men to put an emphasis on economic reasons for developing specializations (t = 0.552, p = 0.011). Students in a more senior year (F = 2.407, p = 0.041) or with a higher average grade put an emphasis on reasons for specializations that are linked to nursing. Discussion and conclusion: Students view specializations as necessary to ensure a sustainable health care system in Slovenia and as an option for continuing their studies.